How to Motivate Whole Blood Donors to Become Plasma Donors. (28th October 2014) - Godin, Gaston; Germain, Marc
Abstract : This study tested the efficacy of interventions to recruit new plasma donors among whole blood donors. A sample of 924 donors was randomized to one of three conditions: control; information only by nurse; and information plus self-positive image message by nurse (SPI). Participants in the control condition only received a leaflet describing the plasma donation procedure. In the two experimental conditions the leaflet was explained face-to-face by a nurse. The dependent variables were the proportion of new plasma donors and the number of donations at six months. Overall, 141 (15.3%) new plasma donors were recruited at six months. There were higher proportions of new plasma donors in the two experimental conditions compared to the control condition (P < . 001 ); the two experimental conditions did not differ. Also, compared to the control condition, those in the experimental conditions (all P s < . 001 ) gave plasma more often ( information only by nurse: d = . 26 ; SPI: d = . 32 ); the SPI intervention significantly outperformed (P < . 05 ) the information only by nurse condition. The results suggest that references to feelings of SPI such as feeling good and being proud and that giving plasma is a rewarding personal experience favor a higher frequency of plasma donation.